Nutritional strategies for promoting fat utilization and delaying the onset of fatigue during prolonged exercise - Lambert, E. V.; Hawley, J. A.; Goedecke, J.; Noakes, T. D.; Dennis, S. C. (Journal of Sports Sciences, 1997)
Carbohydrate ingestion before and during endurance exercise delays the onset of fatigue (reduced power output). Therefore, endurance athletes are recommended to ingest diets high in carbohydrate (70% of total energy) during competition and training. However, increasing the availability of plasma free fatty acids has been shown to slow the rate of muscle and liver glycogen depletion by promoting the utilization of fat. Ingested fat, in the form of long-chain (C16-22) triacylglycerols, is largely unavailable during acute exercise, but medium-chain (C8-10) triacylglycerols are rapidly absorbed and oxidized. We have shown that the ingestion of medium-chain triacylglycerols in combination with carbohydrate spares muscle carbohydrate stores during 2 h of submaximal (<70% VO2 peak) cycling exercise, and improves 40 km time-trial performance. These data suggest that by combining carbohydrate and medium-chain triacylglycerols as a pre-exercise supplement and as a nutritional supplement during exercise, fat oxidation will be enhanced, and endogenous carbohydrate will be spared. We have also examined the chronic metabolic adaptations and effects on substrate utilization and endurance performance when athletes ingest a diet that is high in fat (>70% by energy). Dietary fat adaptation for a period of at least 2-4 weeks has resulted in a nearly two-fold increase in resistance to fatigue during prolonged, low- to moderate-intensity cycling (<70% VO2 peak). Moreover, preliminary studies suggest that mean cycling 20 km time-trial performance following prolonged submaximal exercise is enhanced by 80 s after dietary fat adaptation and 3 days of carbohydrate loading. Thus the relative contribution of fuel substrate to prolonged endurance activity may be modified by training, pre-exercise feeding, habitual diet, or by artificially altering the hormonal milieu or the availability of circulating fuels. The time course and dose-response of these effects on maximizing the oxidative contribution of fat for exercise metabolism and in exercise performance have not been systematically studied during moderate- to high-intensity exercise in humans.